Investigating the Effects of Educational Intervention Based on the Health Belief Model in Adopting Healthy Behaviors by Type 2 Diabetic Patients in 2021 - Mohammad Sarani; Azadeh Heydari; Parvaneh Isfahani (Journal of Research & Health, 2023)
Background: The essential strategies to avoid diabetes complications are lifelong health education and self-care. This study determines the impacts of an educational intervention based on a health belief model. Methods: This quasi-experimental study was conducted on patients with type 2 diabetes using convenience sampling. They were randomly assigned to experimental (n=55) and control groups (n=55). A standard questionnaire was used to collect the data. The healthy behaviors were measured again after 3 and 6 months, and the data analysis was performed using the SPSS software, version 20. Results: The mean value of perceived susceptibility boosted in the intervention group from 18.94 before the training to 22.90 and 22.3 after 3 and 6 months of the intervention, respectively. The mean score perceived severity increased in the intervention group to 31.30 and 31.42 after 3 and 6 months of the intervention, respectively. Meanwhile, the mean score of perceived benefits increased in the intervention group from 10.06 before the training to 11.61 and 13.32 after 3 and 6 months of the intervention, respectively. The mean score of perceived barriers decreased in the intervention group from 19.50 before the training to 13.35 and 12.21 after 3 and 6 months of the intervention, respectively. The mean score of perceived self-efficacy boosted in the intervention group from 24.16 before the training to 29.44 and 29.48 after 3 and 6 months of the intervention, respectively. The mean value of cues to action boosted in the intervention group from 20.15 before the training to 22.2 and 23.2 after 3 and 6 months of the intervention, respectively. Conclusion: The results demonstrated the importance of designing educational programs based on the health belief model constructs over 3 and 6 months in adopting healthy behaviors by subjects with type 2 diabetes.